2015
DOI: 10.3201/eid2110.150912
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ebola Transmission after Rapid Response to Outbreaks in Remote Areas, Liberia, 2014

Abstract: Basic interventions and community acceptance can result in rapid control of outbreaks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 11 publications
2
33
1
Order By: Relevance
“…In a comparison of the effects of six outbreaks that occurred before the introduction of RITE and six that occurred afterward, the time between the first new case in remote areas and the notification of health authorities was reduced by nearly half, the proportion of patients isolated increased from 28% to 81%, survival improved from 13% to 50%, the case reproduction number fell below unity (the replacement rate), outbreaks became shorter (median duration declined from 53 to 25 days), and the number of generations of cases dropped from a median of four to two. 26,27 On their own, these observations made before and after the introduction of RITE do not provide the level of evidence afforded by a randomized trial, but they are consistent with the larger body of evidence on Ebola interventions.…”
Section: Effec T Of Interventionssupporting
confidence: 55%
See 1 more Smart Citation
“…In a comparison of the effects of six outbreaks that occurred before the introduction of RITE and six that occurred afterward, the time between the first new case in remote areas and the notification of health authorities was reduced by nearly half, the proportion of patients isolated increased from 28% to 81%, survival improved from 13% to 50%, the case reproduction number fell below unity (the replacement rate), outbreaks became shorter (median duration declined from 53 to 25 days), and the number of generations of cases dropped from a median of four to two. 26,27 On their own, these observations made before and after the introduction of RITE do not provide the level of evidence afforded by a randomized trial, but they are consistent with the larger body of evidence on Ebola interventions.…”
Section: Effec T Of Interventionssupporting
confidence: 55%
“…22 Empirical evidence of the effect of rapid patient isolation and hospitalization comes from investigations of a series of small outbreaks in Liberia. [23][24][25][26][27] Twelve outbreaks were included in a study of the Rapid Isolation and Treatment of Ebola (RITE) strategy, applied between July and November 2014. RITE encourages active case finding and contact tracing and the use of practices that prevent infection when caring for the ill and burying the dead.…”
Section: Effec T Of Interventionsmentioning
confidence: 99%
“…A study of 15 Ebola outbreaks in Liberia found R  = 1.7; R was reduced to 0.1 after the implementation of immediate isolation or transfer of symptomatic persons to Ebola treatment units, contact identification and monitoring [8]. In this outbreak, all but five confirmed cases were transferred to the Ebola holding center or treatment unit, the time to transfer decreased, and contact identification improved over time.…”
Section: Discussionmentioning
confidence: 99%
“…The need for flexible, mobile, and rapid teams that could quickly reach new hot spots, conduct assessments, and implement early control measures was recognized, leading to development of the RITE strategy (11,12). RITE teams were deployed at the first report of new suspected outbreaks, and team members focused on village-level isolation and management of patients until safe referral to ETUs could be established.…”
Section: Liberiamentioning
confidence: 99%
“…Prefectural Ebola response teams continued to directly observe the contacts each day during the 21-day follow-up period to rapidly isolate newly symptomatic patients. This approach was partially adapted from the Rapid Isolation and Treatment of Ebola (RITE) strategy (11,12) in Liberia and the quarantine village approach from Sierra Leone. WHO declared Guinea free of Ebola transmission on December 29, 2015, after the last Ebola patient in Guinea was discharged from an ETU on November 16, 2015.…”
Section: Guineamentioning
confidence: 99%